Pilot-plant cultivation of Streptomyces griseus producing homologues of nonactin by precursor-directed biosynthesis and their identification by LC/MS-ESI - Rezanka, Tomás; Prell, Ales; Spízek, Jaroslav; Sigler, Karel (The Journal of antibiotics, 2010)
Precursor-directed biogenetic approach was used to produce a range of nonactin homologues in a 50 l fermentor cultivation of strain Streptomyces griseus 34/249 obtained by UV mutagenesis. The production medium contained sodium propionate, isobutyrate and isovalerate as individual precursors, and 10 g l(-1) Diaion HP20 styrene-divinylbenzene resin that maintains suitable precursor concentration by reversibly adsorbing and releasing it. The produced nonactin homologues were separated on two C18 reversed-phase liquid chromatography columns in series and analyzed by MS with ESI source in the positive ion mode. Formation of doubly charged ions was suppressed by an excess of Na(+) ions throughout the process. The production of the homologues increased up to day 5 and then it leveled off. Cultivations with individual precursors yielded a total of 18 nonactin homologues whose spectrum depended on the precursor used. The total production of the homologues was lowered but their spectrum was shifted to higher-molecular-weight compounds.
Keywords: Pentanoic Acids; butyráty; Propionates; isobutyráty; Macrolides; kyseliny pentanové; makrolidy; Butyrates; Chromatography, Liquid; Isobutyrates; Ultraviolet Rays; fermentace; Culture Media; hemiterpeny; hmotnostní spektrometrie s elektrosprejovou ionizací; kultivační média; Fermentation; Streptomyces griseus; Hemiterpenes; propionáty; Spectrometry, Mass, Electrospray Ionization; chromatografie kapalinová; ultrafialové záření